بناء وتقويم التمكين الإداري في مسابح محافظة السليمانية - علي، هاوري جزا; خلف، نصير قاسم; محمود، أراز نوري (جامعة بابل - كلية التربية الرياضية, 2023)
تعد الرياضة وسيلة للتكيف مع متطلبات الحياة العصرية التي ازدادت فيها أهمية الحفاظ على اللياقة البدنية للفرد وتحسين أجهزته الداخلية (العبادي وآخرون، 1989، 58) وقد أصبحت الرياضة تمثل على اختلاف أنشطتها جزءاً هاماً من مكونات قطاع الخدمات. ويهدف البحث بناء مقياس للتمكين الاداري. تقويم عمل إدارات المسابح في التمكين الاداري من وجهة نظر الاداريين في ادارة المسابح في محافظة السليمانية. التعرف على الفروق بين المتوسط الحسابي الفرضي للمقياس ومتوسط عينة البحث في التمكين الإداري. استخدم الباحثون المنهج الوصفي بأسلوب المسح لملاءمته طبيعة البحث تمثل مجتمع الاداريين المسابح في محافظة السليمانية وان عينة البحث يتم جميع الإداريين من ضمن المسابح موجودة داخل محافظة بالغ عددهم (52) المكتوبة رسميا من ضمن الاتحاد الفرعي للسباحة في محافظة السليمانية. و بعد ذلك قام الباحثون توزيع الاستمارة على العينة و بعدها قام الباحثون بتفريغ الاستمارات و حصول على النتائج والبيانات واستخدم الباحثون الوسائل الاحصائية المناسبة لإخراج نتائج البحث واستنتجت الباحثون: ان النتائج ايجابية في كافة مجالات البحث من حيث تقويم التمكين الاداري. وصول الى نتائج ايجابية من حيث العاملين والتدريب والتفويض والفريق العمل والاتصالات الفاعلة. وايضاح مفهوم التمكين لمسؤولي وافراد الهيئة العامة للمسبح، من خلال اللقاءات والاجتماعات Sports are a means of adapting to the requirements of modern life, in which the importance of maintaining the individual’s physical fitness and improving his internal systems has increased (Al-Abadi et al., 1989, 58). Sports, with its various activities, have become an important part of the components of the service sector. The research aims to build a measure of administrative empowerment. Evaluating the work of swimming pools departments in administrative empowerment from the point of view of administrators in the swimming pools administration in Sulaymaniyah Governorate. Identifying the differences between the hypothesized arithmetic mean of the scale and the mean of the research sample on administrative empowerment. The researchers used the descriptive approach in the survey style because it suits the nature of the research. It represents the community of swimming pool administrators in Sulaymaniyah Governorate, and the research sample includes all administrators who are among the swimming pools located within the governorate. Their number is (25) and they are officially registered within the Swimming Sub-Union in Sulaymaniyah Governorate. After that, the researchers distributed the form to the sample, and then the researchers unpacked the forms and obtained the results and data. The researchers concluded that positive results were reached in terms of administrative building in all Sulaymaniyah swimming pools. The results were positive in all areas of research in terms of evaluating administrative empowerment. Positive results were achieved in terms of employees, training, delegation, work team, and effective communications. Explaining the concept of empowerment to officials and members of the General Authority of the Swimming Pool, through meetings and conferences
Keywords: التمكين الإداري -- الإدارة الرياضية -- إدارات المسابح -- الأنشطة الرياضية -- العراق